Cross-cutting topic introduction in teaching Journalism: the case of solidarity - Monedero Morales, Carmen del Rocío; Olmedo Salar, Silvia (Historia y Comunicación Social, 2014)
The entry into force of the European Higher Education Area (EHEA) has made a commitment to training for the acquisition of skills, enabling and promoting students professional performance. To meet these objectives the training process must be accompanied by practice to foster the development of values that nurture citizen’s role, as in the case of solidarity. The text presented addresses the innovative experience made with students of second course of the degree in Journalism (course 2012/13). Also the keys that it shows could be extrapolated to other subjects in the field of Social Sciences.